Strategi Guru Dalam Mengatasi Kecemasan Berbicara (Language Anxiety) Siswa Pada Pelajaran Bahasa Indonesia Di SMP Negeri 14 Kota Bengkulu - Yuliarti, Yuda; Andra, Vebbi; Friantary, Heny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skills are one of the crucial productive competencies in Indonesian language learning, but affective barriers in the form of language anxiety are often a major obstacle for junior high school students. This study aims to describe and analyze the strategies used by Indonesian language teachers in overcoming students' speaking anxiety at SMP Negeri 14 Bengkulu City based on empirical data during the teaching internship period. The research method used is descriptive qualitative with a case study approach. Data were collected through participatory observation techniques when the researcher acted directly as a teacher, in-depth interviews with subject teachers, and documentation studies. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The results showed two main findings. First, the manifestation of students' anxiety in class predominantly appears in the form of psychological resistance behavior, such as refusing to come to the front of the class due to low self-efficacy, sudden nervousness accompanied by physical indications (soft voice and trembling lips), and the tendency to shift responsibility by pointing at other friends to avoid negative social evaluation caused by the fear of making mistakes. Second, teachers implement a three-pillar handling strategy, namely preventive action through conditioning small group work methods, curative action through the enforcement of